The SpoMBe pathway drives membrane bending necessary for cytokinesis and spore formation in yeast meiosis - Maier, Peter; Maeder, Céline; Stelzer, Ernst H. K.; Knop, Michael (The EMBO journal, 2008)
Precise control over organelle shapes is essential for cellular organization and morphogenesis. During yeast meiosis, prospore membranes (PSMs) constitute bell-shaped organelles that enwrap the postmeiotic nuclei leading to the cellularization of the mother cell's cytoplasm and to spore formation. Here, we analysed how the PSMs acquire their curved bell-shaped structure. We discovered that two antagonizing forces ensure PSM shaping and proper closure during cytokinesis. The Ssp1p-containing coat at the leading edge of the PSM generates a pushing force, which is counteracted by a novel pathway, the spore membrane-bending pathway (SpoMBe). Using genetics, we found that Sma2p and Spo1p, a phospholipase, as well as several GPI-anchored proteins belong to the SpoMBe pathway. They exert a force all along the membrane, responsible for membrane bending during PSM biogenesis and for PSM closure during cytokinesis. We showed that the SpoMBe pathway involves asymmetric distribution of Sma2p and does not involve a GPI-protein-containing matrix. Rather, repulsive forces generated by asymmetrically distributed and dynamically moving GPI-proteins are suggested as the membrane-bending principle.